(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Mud crab Scylla serrata is one of crustacean commodities with high economic value. One of the unsolved obstacles in mud crabs cultivation is crabs’ stress level caused by the declining water quality. The recirculating system is a method for maintaining water quality throughout the rearing period of culture crab. This system can use a variety of physical filter materials, such as zeolite, sand, and other materials. This study aimed to determine the amount of malang sand as a physical filter which positively affect the physiological responses and production performance of mud crabs. This research was carried out using a recirculating system with a completely randomized design conducted in five treatments with three replicates, i.e., malang sand with a weight of 0 kg (control), 5 kg, 10 kg, 15 kg, and 20 kg. The results proved that the best physiological response and production performance of mud crab was observed at malang sand treatment with a weight of 5 kg. This treatment showed specific growth rate, absolute growth rate for body weight, absolute growth rate for body length, and the survival rate of mud crabs with the highest value of 0.18±0.061%, 0.13±0.05 g/day, 0.0016±0.00006 cm/day, and 77.77%, respectively, yet it had the lowest feed conversion ratio of 3.76±004. In addition, the 5 kg treatment had water quality parameters in the tolerable ranges for mud crabs’ growth.